PENGARUH PENAMBAHAN UBI JALAR UNGU TERHADAP KUALITAS ES KRIM - Kurniawan, Erik; Faridah, Anni; Holinesti, Rahmi (Journal of Home Economics and Tourism, 2014)
The use of purple sweet potato in food processing is an attempt to diversify the food, one of which is in the processing of ice cream. This study aimed to analyze the effect of different composition of purple sweet potato as much as 15%, 20%, and 25%, the quality of the ice cream. This research was an experiment using a completely randomized design with three replications by 30 panelis. The results of the hypothesis test showed influence on the level of the commission of the third. The quality level of the test was a better color on the addition of 25%, better flavor, namely the addition of 15%, better texture, namely the addition of 15% and a better sense that the addition of 15%. Hedonic test quality better color namely the addition of 25%, better flavor is the addition of 15%, better texture, namely the addition of 15% and a better sense that the addition of 15%. Keywords : Quality Ice cream, Sweet Potato purple.